Transcranial magnetic stimulation as an investigative tool for motor dysfunction and recovery in stroke: an overview for neurorehabilitation clinicians - Cortes, Mar (2012)
RATIONALE: An improved understanding of motor dysfunction and recovery after stroke has important clinical implications that may lead to the design of more effective rehabilitation strategies for patients with hemiparesis. SCOPE: Transcranial magnetic stimulation (TMS) is a safe and painless tool that has been used in conjunction with other existing diagnostic tools to investigate motor pathophysiology in stroke patients. Since TMS emerged over two decades ago, its application in clinical and basic neuroscience has expanded worldwide. TMS can quantify the corticomotor excitability properties of clinically affected and unaffected muscles, and probe local cortical networks, as well as remote but functionally related areas. This provides novel insight into the physiology of neural circuits underlying motor dysfunction, and brain reorganization during the motor recovery process. This important tool needs to be used with caution by clinical investigators, its limitations need to be understood and the results should be interpreted along with clinical evaluation in this patient population. SUMMARY: In this review, we provide an overview of the rationale, implementation and limitations of TMS to study stroke motor physiology. This knowledge may be useful to guide future rehabilitation treatments by assessing and promoting functional plasticity.